FINANCIAL TECHNOLOGY DAN GAYA HIDUP DALAM PERILAKU KEUANGAN MAHASISWA POLITEKNIK NEGERI UJUNG PANDANG - Tjambolang, Tjare A; Radjab, Enny; Hamid, Abd (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The purpose of this study is to evaluate the impact of financial technology services and lifestyle on the financial behavior of Ujung Pandang State Polytechnic (PNUP) students. The population in this study were all Ujung Pandang State Polytechnic (PNUP) students. The sample was determined using a purposive sampling technique, the sample size was determined using the Slovin formula, and the sample size was 99 respondents. Data was collected by distributing questionnaires. Validity and reliability tests in this research were carried out using the SPSS version 24.0 program. The research findings indicate that both financial technology service (X1) and the lifestyle variable (X2) has an impact on the student’s financial behaviour(Y) at Politeknik Negeri Ujung Pandang